EUs oversøiske lande og territorier: postkoloniale suverænitetsspil og Grønlands arktiske muligheder - Gad, Ulrik Pram; Hannibal, Ida; Holst, Kristine; Adler-Nissen, Rebecca (Politik, 2011)
How do former colonies such as Greenland get a voice in international relations? The European Union (EU) is currently revising its relations to the member states’ overseas countries and territories (OCTs). EU seeks to reform its relations to the OCTs so that it builds on a ‘mutually bene tting’ and ‘post-modern’ coopera- tion. Drawing on a rhetorical approach to the notion of ‘sovereignty games’, the article demonstrates that Greenland’s response to the reform proposal differs from that of the other OCTs. Greenland articulates the future relation as one between equals, where both parties give and take. In contrast, the other OCTs remain within a post-colonial discourse of unilateral aid. Geostrategic considerations coupled with unused resources and possibilities in the Arctic are central to Greenland’s ‘Westphalian’ and confident response to the EU.